ANALYSIS OF THE ADVERTISING DISCOURSE, FROM THE GRAPHIC AND SEMIOTICAL PERSPECTIVES, OF THE ADVERTISING DISPLAYED IN THE COMMERCIAL PREMISES OF THE LEATHER, FOOTWEAR AND LEATHER GOODS CLUSTER, IN THE RESTAURANT SECTOR OF THE CITY OF BOGOTÁ IN COLOMBIA (International Seven Journal of Multidisciplinary, 2025)
The Restrepo neighborhood is found in the Antonio Nariño locality, in the south east of Bogotá, capital of Colombia. It was founded in the 1930s, thanks to the settlements of migrant workers from peripheral rural areas. Since its birth it has been considered a working-class neighborhood, perhaps for the same reason it is located in the south end of the city.  Later, the neighborhood gained popularity from a church, a farmer’s market and the number of shoe repairers and manufacturers. These shoemakers located their commercial premises and factories, on many occasions, inside their homes, from where they advertised their products and services at free will; in such a way that, a purely popular advertising discourse was generated. Based on this context, the present investigation defines its objective as to analyze the advertising discourse, from the graphic and semiotic perspectives, of the advertising displayed in the commercial premises of the leather, footwear and leather goods cluster of the sector. The research has a qualitative approach, a transversal moment, with an intentional sampling and a descriptive scope, with a selection of sixty-one commercial premises. In order to collect the information, an instrument was divided into two parts. The first one addressed the semiotic from Jakobson (1975), Barthes (1970) and Péninou (1976); the second instrument has its focus on graphic analysis of the elements of popular culture (Figueroa, 2007), the graphics of urban media (Brito et al., 2011) and the sociocultural artifacts associated with graphic pieces (Chaparro, 2013). As a result, it was found that the functions of the message are present (Jakobson, 1975), differentiated messages were evident (Barthes, 1970), as well as the functions of the advertising message (Péninou, 1976) in all the stores. On the other hand, it was determined that the relationship with the names of the owners of the premises, word contractions and foreign words, are the rule. Likewise, the nominative act is determined by a series of beliefs, superstitions and taboos. As a conclusion, there is a presence of great graphic and textual saturation, where the passer-by is flooded with information.